Analisis Efektivitas Sistem Pengendalian Internal Terhadap Pengelolaan Kas Melalui Cash Opname - Wea, Theresia; Nona Dince, Maria; Libu Lamawitak, Paulus (Jurnal Projemen UNIPA, 2026)
An internal control system is a system consisting of an organizational structure, plans, methods, and coordinated procedures that help safeguard company assets, improve operational effectiveness and efficiency, and support the implementation of regulations established by management.This study aims to analyze the effectiveness of the implementation of internal control systems in cash management through the cash opname mechanism at KSP Kopdit Tuke Jung Head Office Nelle. Data collection in this study used interview, observation, and documentation methods. This study uses a qualitative descriptive approach referring to the COSO (Committee of Sponsoring Organizations of the Treadway Commission) components, which consist of five components, namely control environment, risk assessment, control activities, information and communication, and monitoring. The research results show that the effectiveness of the internal control system in cash management through cash opname has been implemented but has not fully met the five components of the internal control system according to COSO. The elements that have not been fulfilled are control activities, information and communication, and monitoring. Nevertheless, some components of the internal control system implemented at KSP Kopdit Tuke Jung have been operating effectively.